A core outcome domain set for clinical research on capillary malformations (the COSCAM project): an e‐Delphi process and consensus meeting. (31st July 2022) - Langbroek, Ginger Beau; Wolkerstorfer, Albert; Horbach, Sophie E.R.; Spuls, Phyllis I.; Kelly, Kristen M.; Robertson, Susan J.; van Raath, M. Ingmar; Al‐Niaimi, Firas; Kono, Taro; Boixeda, Pablo; Laubach, Hans J.; Badawi, Ashraf M.; et al.
Summary: Background: There is limited evidence on the best available treatment options for capillary malformations (CMs), mainly due to the absence of uniform outcome measures in trials on therapies. A core outcome set (COS) enables standard reporting of trial outcomes, which facilitates comparison of treatment results. Objectives: To develop a core outcome domain set (CDS), as part of a core outcome set (COS), for clinical research on CMs. Methods: Sixty‐seven potentially relevant outcome subdomains were recognized based on the literature, focus group sessions, and input from the COSCAM working group. These outcome subdomains were presented in an online Delphi study to CM experts (medical specialists and authors of relevant literature) and (parents of) patients with CM (international patient associations). During three e‐Delphi study rounds, the participants repeatedly scored the importance of these outcome subdomains on a seven‐point Likert scale. Participants could also propose other relevant outcome subdomains. Consensus was defined as ≥ 80% agreement as to the importance of an outcome subdomain among both stakeholder groups. The CDS was finalized during an online consensus meeting. Results: In total 269 participants from 45 countries participated in the first e‐Delphi study round. Of these, 106 were CM experts from 32 countries, made up predominantly of dermatologists (59%) and plastic surgeons (18%). Moreover, 163 (parents of) patients with CM from 28 countries participated, of whom 58% had Sturge–Weber syndrome. During the two subsequent e‐Delphi study rounds, 189 and 148 participants participated, respectively. After the entire consensus process, consensus was reached on 11 outcome subdomains: colour/redness, thickness, noticeability, distortion of anatomical structures, glaucoma, overall health‐related quality of life, emotional functioning, social functioning, tolerability of intervention, patient satisfaction with treatment results, and recurrence. Conclusions: We recommend the CDS to be used as a minimum reporting standard in all future trials of CM therapy. Our next step will be to select suitable outcome measurement instruments to score the core outcome subdomains. What is already known about this topic? Besides physical and functional sequelae, capillary malformations (CMs) often cause emotional and social burden. The lack of uniform outcome measures obstructs proper evaluation and comparison of treatment strategies. As a result, there is limited evidence on the best available treatment options. The development of a core outcome set (COS) may improve standardized reporting of trial outcomes. What does this study add? A core outcome domain set (CDS), as part of a COS, was developed for clinical research on CMs. International consensus was reached on the recommended core outcome subdomains to be measured in CM trials: colour/redness, thickness, noticeability, distortion of anatomical structures, glaucoma, overall health‐related quality of life, emotional functioning, social functioning, tolerability of intervention, patient satisfaction with treatment results, and recurrence. This CDS enables the next step in the development of a COS, namely to reach consensus on the core outcome measurement instruments to score the core outcome subdomains. What are the clinical implications of this work? The obtained CDS will facilitate standardized reporting of treatment outcomes, thereby enabling proper comparison of treatment results. This comparison is likely to provide more reliable information for patients about the best available treatment options. Abstract : A core outcome domain set (CDS) was developed for clinical research on capillary malformations, to improve standardized reporting of trial outcomes on therapies in the future. By means of an e‐Delphi study and online consensus meeting consensus was reached on 11 outcome subdomains. We recommend the CDS to be used as a minimum reporting standard in all future therapy trials on capillary malformations. Linked Comment: H. Rönsch and J. Kottner. Br J Dermatol 2022; 187:629–630 . Plain language summary available online